Scintillation 2D-matrices for digital tomography - Voronkin, E.F.; Ryzhikov, V.D.; Grinyov, B.V.; Shevchenko, E.Y. (Functional Materials, 2015)
A possibility is shown of tomography applications of scintillation 2D matrices based on aluminum-doped zinc selenide (ZnSe(Al)). Procedures for preparation of multi-element matrices are described, as well as results on inter-element interference. For the first time, chalcogenide scintillators based on zinc selenide were tested on biological objects (blood vessels) at ”Filips”, Israel, for detection of cholesterol plaques.